Hyperion's Asterisks: Seeing Stars & Star Power. Issue 2 (4th March 2022) - Bates, Brian
ABSTRACT: Hyperion. A Fragment closes Keats's 1820 volume with fourteen asterisks, but why? Who added them, and to what effect? Romantic period scholars have not interpreted Hyperion 's asterisks as significant typography in the 1820 volume. Most often, the asterisks have been left out of critical studies of the poem or treated as a reiteration of its subtitle. The major critical sticking point has been determining Keats's authorial intentions. In this essay, I aim to shift our focus from defending Keats's intentions to considering why Keats's publishing team, led by John Taylor, would want to end the 1820 volume with fourteen asterisks. I propose that the asterisks mark their hopes for Hyperion 's positive reception and Keats's career advancement, and not Keats's incapacity to finish the poem. Hyperion 's asterisks have particular significations and rhetorical effects in the 1820 volume. I want to emphasize that these asterisks were legible to early nineteenth-century readers and that Keats's publishers sought to capitalize on that legibility with a Gothic twist. I argue that Hyperion 's asterisks connect the potential of Keats's unfinished poem with legends of star poets and promote his rising star power in the spectacular light of Apollo's transformation into the sun god of poetry.